Reproduction of Different Religious Family Cultures in Instilling Religious and Social Values in Children - Persada, Lingga Yudistira Raka; Wicaksono, Harto (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The phenomenon of interfaith marriage tends to raise problems regarding how parents provide parenting patterns to their children. These issues include how parents will raise their children to instill religious and social values while adapting to environmental conditions. This article aims to determine the reproduction of interfaith family culture in instilling religious and social values in children. The study used a qualitative method in the form of a case study of interfaith families, with field research in Kapencar Village, Semarang City, and Bekasi City. This study focused on 12 informants from three families of different religions. Data has been collected through interviews and field observations on May 21, 2024, and August 1, 2024. The study was analyzed using Pierre Bourdieu's theory of cultural reproduction which cannot be separated from the concept of social practice. This theory is used to examine the cultural reproduction produced by families of different religions by considering the aspects of capital, habitus, and arena within the family. The results of the study show that interfaith families produce complex values by instilling them in children. In instilling religious and social values in interfaith families, it is possible to reproduce symbolic dominance and innovative cultural reproduction. The reproduction of symbolic dominance includes aspects of giving values that tend to be dominated by one of the parents' religions and the reproduction of innovative culture includes aspects of giving mutually balanced values. There are value instillation strategies found in interfaith families, namely a universal value-based model and a model of dividing the role of parents in instilling religious and social values. This research serves as a reference for understanding and developing parenting patterns in families of various religious backgrounds.